2016
DOI: 10.4103/2045-9912.196900
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of hyperbaric oxygen therapy in a juvenile rat model of repetitive mild traumatic brain injury

Abstract: Repetitive mild traumatic brain injury (rmTBI) is an important medical concern for adolescent athletes that can lead to long-term disabilities. Multiple mild injuries may exacerbate tissue damage resulting in cumulative brain injury and poor functional recovery. In the present study, we investigated the increased brain vulnerability to rmTBI and the effect of hyperbaric oxygen treatment using a juvenile rat model of rmTBI. Two episodes of mild cortical controlled impact (3 days apart) were induced in juvenile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…Huang et al. () who applied HBO 1 h/day × 3 days at 2 ATA were able to demonstrate in a rat model that HBO significantly decreased MRI‐identified abnormalities and tissue histopathology after repetitive mild traumatic brain injury. Yu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al. () who applied HBO 1 h/day × 3 days at 2 ATA were able to demonstrate in a rat model that HBO significantly decreased MRI‐identified abnormalities and tissue histopathology after repetitive mild traumatic brain injury. Yu et al.…”
Section: Discussionmentioning
confidence: 99%
“…HBO, administering pure oxygen at a pressure greater than that of atmosphere, was demonstrated to improve neurological outcomes in the setting of brain injury via the mechanisms of cellular metabolism benefit, anti‐inflammation, anti‐apoptosis, and blood–brain barrier (BBB) preservation (Buckley, Juurlink, Isbister, Bennett, & Lavonas, ; Cossu, ; Hu, Feng, & Xi, ; Huang, Boling, & Zhang, ; Huang & Obenaus, ; Huang, Obenaus, Hamer, & Zhang, ; Ostrowski, Stepien, Pucko, & Matyja, ). Although HBO has been applied as one of the arousal procedures in patients with prolonged coma (Jiang et al, ), few study investigated the direct arousal effect of HBO and the potential underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…There has also been emerging research on the different types of therapy for patients post TBI. Examples include hyperbaric oxygen therapy, hypothermia therapy and transcranial light therapy [ 90–94 ]. Specifically for rmTBI, Huang and colleagues found that rats subjected to rmTBI (two injuries with a 3-day interinjury interval) treated with daily hyperbaric oxygen therapy during the interinjury period had reduced histopathological gliosis and pathological MRI finding associated with the second injury [ 90 ].…”
Section: Summary and Future Perspectivementioning
confidence: 99%
“…Examples include hyperbaric oxygen therapy, hypothermia therapy and transcranial light therapy [ 90–94 ]. Specifically for rmTBI, Huang and colleagues found that rats subjected to rmTBI (two injuries with a 3-day interinjury interval) treated with daily hyperbaric oxygen therapy during the interinjury period had reduced histopathological gliosis and pathological MRI finding associated with the second injury [ 90 ]. Further, rats exposed to rmTBI (two injuries) that were treated with 1-h of hypothermia an hour after the second injury had axons with decreased APP density compared with the untreated group [ 93 ].…”
Section: Summary and Future Perspectivementioning
confidence: 99%